Community general practitioner. - Mant, D; Anderson, P (1985)
The attainment of quality in general practice entails explicit recognition of the public-health content of primary care. General practitioners should accept responsibility for auditing the state of the practice health, monitoring and controlling environmental disease, planning local services, auditing the effectiveness of preventive programmes, and evaluating the population effects of medical intervention. This requires specific training in the skills of population medicine, reallocation of scarce resources, and cooperation with existing public-health doctors. Eventual integration of community medicine and general practice is desirable.